2011
DOI: 10.5799/ahinjs.02.2011.02.0013
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and behaviors of Family Physicians regarding use of antibiotics

Abstract: Objectives: Antimicrobials are the most widely used drug groups and antibiotic resistance due to irrational antimicrobial usage is a major problem in the world. The aim of this study is to evaluate attitudes of family physicians antimicrobial prescribing. Materials and methods:This study was conducted in November 2006 in Bolu and Duzce provinces where the first family physician practices were initiated in Turkey. The records of family physicians were reviewed retrospectively. Patients' data, social security in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 4 publications
(3 reference statements)
1
11
0
2
Order By: Relevance
“…In our research it was found that cephalosporins accounted 31.78% of total antibiotic prescriptions which is high as compared to the study conducted in Nepal and Turkey but low than India [7,8,19]. The highest uses were by cefixime, cefuroxime and ceftriaxone for respiratory infections and other infections.…”
Section: Discussionmentioning
confidence: 50%
“…In our research it was found that cephalosporins accounted 31.78% of total antibiotic prescriptions which is high as compared to the study conducted in Nepal and Turkey but low than India [7,8,19]. The highest uses were by cefixime, cefuroxime and ceftriaxone for respiratory infections and other infections.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, antibiotics were the major drug class prescribed in children of which cephalosporin accounted 20% of total antibiotic use. It was high as compared to the study conducted in Nepal and Turkey but lower than that of India [30][31][32]. In Bangladesh, all the antibiotics were prescribed on the basis of patient's complaints and also the antibiotics were used in inappropriate doses and durations particularly among the children under-five [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic prescriptions were found to be the highest in PrHs (42.6%), followed by PHCs (40.7%), PbHs (35.2%), and UHs (35.2%) ( Table 4). In a study of primary health care in Turkey, 25.9% of all patients were prescribed antibiotics [6]. In another study conducted on primary health care in Turkey, nearly half of the physicians (48.4%) stated that they had written antibiotics on one of every three prescriptions (30%) [28].…”
Section: Discussionmentioning
confidence: 99%
“…The irrational use of medicines is one of the most important problems in Turkey and many other countries [3][4][5][6][7][8][9][10]. With the "Health Transformation Program" implemented in 2003, the Turkish Ministry of Health (MoH) has identified strategies towards the elimination of such irrational use.…”
Section: Introductionmentioning
confidence: 99%